Engineering thick cell sheets by electrochemical desorption of oligopeptides on membrane substrates - Enomoto, Junko (Regen Ther, 2016)
We developed a gold-coated membrane substrate modified with an oligopeptide layer that can be used to grow and subsequently detach a thick cell sheet through an electrochemical reaction. The oligopeptide CCRRGDWLC was designed to contain a cell adhesive domain (RGD) in the center and cysteine residues at both terminals. Cysteine contains a thiol group that forms a gold–thiolate bond on a gold surface. Cells attached to gold-coated membrane substrates via the oligopeptide layer were readily and noninvasively detached by applying a negative electrical potential to cleave the gold–thiolate bond. Because of the effective oxygen supply, fibroblasts vigorously grew on the membrane substrate and the thickness of the cell sheets was ∼60 μm at 14 days of culture, which was 2.9-fold greater than that of cells grown on a conventional culture dish. The cell sheets were detached after 7 min of electrical potential application. Using this approach, five layers of cell sheets were stacked sequentially with thicknesses reaching >200 μm. This approach was also beneficial for rapidly and readily transplanting cell sheets. Grafted cell sheets secreted collagen and remained at the transplanted site for at least 2 months after transplantation. This simple electrochemical cell sheet engineering technology is a promising tool for tissue engineering and regenerative medicine applications.